Arbitrary lagrangian-eulerian form of flowfield dependent variation method for moving boundary problems - Zulkifli, Mohd fadhli; Omar, Ashraf Ali; Asrar, Waqar (2014)
A novel numerical scheme using the combination of Flowfield Dependent Variation (FDV) method and Arbitrary Lagrangian-Eulerian (ALE) method is developed. This method is a mixed explicit-implicit numerical scheme and its implicitness is dependent on the physical properties of the flowfield. The scheme, which is named ALE-FDV method, is discretized using finite volume method in order to give flexibility in dealing with complicated geometries. The formulation itself yields a sparse matrix, which can be solved using any iterative algorithm for linear systems of algebraic equations. Several cases of moving boundary problems in two-dimensional inviscid and viscous flows have been selected as benchmark problems in order to validate the method. Good agreement with available experimental and numerical data in the literature has been obtained, thus showing promising application in complex fluid-structure interaction problems.